Excision of 8-oxoguanine within clustered damage by the yeast OGG1 protein. - David-Cordonnier, M; Boiteux, S; O'Neill, P (2001)
Clustered damages are formed in DNA by ionising radiation and radiomimetic anticancer agents and are thought to be biologically severe. 7,8-dihydro-8-oxoguanine (8-oxoG), a major DNA damage resulting from oxidative attack, is highly mutagenic leading to a high level of G.C-->T.A transversions if not previously excised by OGG1 DNA glycosylase/AP lyase proteins in eukaryotes. However, 8-oxoG within clustered DNA damage may present a challenge to the repair machinery of the cell. The ability of yeast OGG1 to excise 8-oxoG was determined when another type of damage [dihydrothymine, uracil, 8-oxoG, abasic (AP) site or various types of single-strand breaks (SSBs)] is present on the complementary strand 1, 3 or 5 bases 5' or 3' opposite to 8-oxoG. Base damages have little or no influence on the excision of 8-oxoG by yeast OGG1 (yOGG1) whereas an AP site has a strong inhibitory effect. Various types of SSBs, obtained using either oligonucleotides with 3'- and 5'-phosphate termini around a gap or through conversion of an AP site with either endonuclease III or human AP endonuclease 1, strongly inhibit excision of 8-oxoG by yOGG1. Therefore, this large inhibitory effect of an AP site or a SSB may minimise the probability of formation of a double-strand break in the processing of 8-oxoG within clustered damages.